(3Gdedd hGdOhd aj GdCMcGe heG JOd Ydjg GdCTNGU GdYdhjI hJCKjQGJgG aj GdCLSGe GdSadjIs - (3LYaQ Hf eMeO Hf YeQ GdHdNj, CHh eYTQ , nCoHh nerYnTQ Gdnandcj,J (B272 (3g` s
(3ChdgG (B:s
(3gPG cJGH ai Led ef OdGdGJ GdGTNGU GdYdhjI Ydi GdGMOGK GdSadjI GdcGFfI aiYGde Gdchf ef LgI aSGOgG hUdGMgG s
(3BNQgG (B:s
(3hcPdc Gdbhd ai GdGTNGU GdYGdjI ai GdGReGf GdJMhjdjI adfced GdaUd GdKGfi ef GdebGdI GdKGefI hGdMeO ddg s
(3Vef eLehY s
(3HGdOGNd HYV ChQGb Hbde eNJdas
(3HgG HYV GdCTcGds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B148s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B221 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B395 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B965s
Keywords: (3Gdadcs